Implementation of the Concept of Tarbiyah in the Islamic Education Curriculum - Yenni Zuraidah; Sofvia Rianti; Jalwa Suci Rahmadani (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2024)
Islamic education has a broader goal than simply transferring knowledge, namely forming morals and spirituality that are in accordance with religious teachings. The concept of tarbiyah, which means educating, nurturing and nurturing, emphasizes the formation of Islamic character through a curriculum based on the Koran and Al-Hadith. This research aims to understand and evaluate the implementation of the tarbiyah concept in the Islamic religious education curriculum in madrasas. Through a qualitative descriptive approach, data was obtained from interviews, observations and documentation involving several madrasa teachers. The research results show that the tarbiyah concept is integrated through learning methods and daily activities that reflect Islamic values. Even though there are challenges in its implementation, such as limited time and lack of support from the environment outside the school, regular evaluations of the effectiveness of tarbiyah show that this approach is effective in shaping students' Islamic character. This research provides an important contribution in understanding how the Islamic religious education curriculum can form individuals who have noble character, faith, and are ready to face the challenges of the times as God's caliphs on earth.